1993
DOI: 10.1063/1.465063
|View full text |Cite
|
Sign up to set email alerts
|

Nonadiabatic effects in the photodissociation of H2S in the first absorption band: An ab initio study

Abstract: The photodissociation of H2S through excitation in the first absorption band (λ≊195 nm) is investigated by means of extensive ab initio calculations. Employing the MRD-CI method we calculate the potential energy surfaces for the lowest two electronic states of 1A″ symmetry varying both HS bond distances as well as the HSH bending angle. (In the C2v point group these states have electronic symmetry 1B1 and 1A2, respectively.) The lower adiabatic potential energy surface is dissociative when one H atom is pulled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
100
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(113 citation statements)
references
References 66 publications
13
100
0
Order By: Relevance
“…Their ab initio calculations 61 covered a broad area of configuration space for the coupled 1 1 A′′/2 1 A′′ states, ground state (1 1 A′) as well as TDM surfaces, followed by construction of a sequence of interpolated PESs for the three diabats, adiabats, and TDM surfaces. In fact, their calculations allowed a satisfactory description of the first absorption band of H 2 S. However, as noted in ref 48, the resulting mixing angles do not show a correct asymptotic behavior, with the diabats not merging the adiabats at the atom-diatom dissociation limits. Using a similar diabatization scheme, Dobbyn and Knowles 38 have reported the same difficulty in a study of the 1 A′ states of the water molecule.…”
Section: Global Multisheeted Approaches Employing Diabatization Schemmentioning
confidence: 99%
See 4 more Smart Citations
“…Their ab initio calculations 61 covered a broad area of configuration space for the coupled 1 1 A′′/2 1 A′′ states, ground state (1 1 A′) as well as TDM surfaces, followed by construction of a sequence of interpolated PESs for the three diabats, adiabats, and TDM surfaces. In fact, their calculations allowed a satisfactory description of the first absorption band of H 2 S. However, as noted in ref 48, the resulting mixing angles do not show a correct asymptotic behavior, with the diabats not merging the adiabats at the atom-diatom dissociation limits. Using a similar diabatization scheme, Dobbyn and Knowles 38 have reported the same difficulty in a study of the 1 A′ states of the water molecule.…”
Section: Global Multisheeted Approaches Employing Diabatization Schemmentioning
confidence: 99%
“…In an early attempt to establish a purely first-principles understanding of the photodissociation of H 2 S, Heumann et al 48 suggested a procedure for constructing mixing angles by exploring at each geometry the CI coefficients of the reference configurations that have the desired diabatic character at the locus of C 2V symmetry. Their ab initio calculations 61 covered a broad area of configuration space for the coupled 1 1 A′′/2 1 A′′ states, ground state (1 1 A′) as well as TDM surfaces, followed by construction of a sequence of interpolated PESs for the three diabats, adiabats, and TDM surfaces.…”
Section: Global Multisheeted Approaches Employing Diabatization Schemmentioning
confidence: 99%
See 3 more Smart Citations